Impaired hippocampal neurogenesis associated with regulatory ceRNA network in a mouse model of postoperative cognitive dysfunction - Jingrun Lin; Xiaoqiu Zhu; Xuan Li; Yu Hong; Yaohui Liang; Siqi Chen; Chenzhuo Feng; Lin Cao (BMC Anesthesiology)
Abstract Background Postoperative cognitive dysfunction (POCD) represents a post-surgical complication that features progressive cognitive impairment and memory loss, often occurring in elderly patients. This study aimed to investigate the potential biological mechanisms underlying POCD. Methods Male C57BL/6 mice (2 and 17 months old) were randomly assigned to surgery or control groups. The surgery group underwent laparotomy under 1.5% isoflurane anesthesia, while controls received no intervention. Cognitive function was assessed 7–10 days post-surgery using open field, Y-maze, and novel object recognition tests. Hippocampal mRNA expression was analyzed using Encyclopedia of Genes and Genomes (KEGG) and Gene Ontology (GO) enrichment. A competing endogenous RNA (ceRNA) network was constructed using microRNA (miRNA) target prediction databases (miRanda, miRTarbase, miRcode) and sequencing results. Key findings were validated by RT-qPCR and immunofluorescence. The Connectivity Map (CMap) database was queried to predict potential POCD treatments. Results Aging significantly affected mice’s spontaneous activity in the open field test (F1, 28 = 8.933, P < 0.01) and the proportion of time spent in the center area (F1, 28 = 5.387, P < 0.05). Surgery significantly reduced the rate of spontaneous alternations in the Y-maze (F1, 28 = 16.94, P < 0.001) and the recognition index in novel object recognition test (F1, 28 = 6.839, P < 0.05) in aging mice, but had no effect on young mice. Transcriptome analysis revealed that aging and surgery downregulated multiple neurogenesis-related genes in the hippocampus. Doublecortin (DCX) immunofluorescence staining confirmed reduced hippocampal neurogenesis in aging mice, which was further decreased after surgery. We identified several key lncRNAs and miRNAs implicated in neurogenesis regulation. Additionally, drugs were predicted as potential therapeutic candidates for POCD treatment. Conclusion Both aging and surgery have complex effects on the hippocampal transcriptome in mice. The significant decrease in neurogenesis may be a potential reason for the increased susceptibility of aging mice to POCD. The identified key regulatory lncRNAs, miRNAs, and drugs provide potential therapeutic targets for POCD prevention and treatment.